2019
DOI: 10.1021/acsenergylett.9b00460
|View full text |Cite
|
Sign up to set email alerts
|

New Random Copolymer Acceptors Enable Additive-Free Processing of 10.1% Efficient All-Polymer Solar Cells with Near-Unity Internal Quantum Efficiency

Abstract: Finding effective molecular design strategies to optimize the active layer blend morphology is among the long-standing challenges in developing efficient allpolymer solar cells (all-PSCs). Here we show that new biselenophene/selenophenelinked naphthalene diimide random copolymer acceptors BSSx (x = 10, 20, 50) facilitate the achievement of high-performance all-PSCs without the use of any solution processing additive. Blends of BSS10 with donor polymer PBDB-T combined 10.1% power conversion efficiency with 97% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 61 publications
3
119
0
Order By: Relevance
“…Figure summarizes the representative high‐performance polymer acceptors enabling PCEs over 8% in all‐PSCs reported in literature together with their optical bandgap ( E g opt ) and absorption coefficient (ε) . Recently, with the extensive efforts dedicated to polymer design and device optimization, Huang and co‐workers and Jenekhe and co‐workers have achieved all‐PSC performance with PCE greater than 10% using poly(naphthelene diimide‐ alt ‐bithiophene) (N2200) and BSS10 as the acceptor, respectively (Figure a). However, most of the NDI‐ and PDI‐based polymer acceptors exhibit ε values about 3.0–4.8 × 10 4 cm −1 , which are greatly lower than those (1.0–1.3 × 10 5 cm −1 ) of typical nonfullerene small molecules .…”
Section: Figurementioning
confidence: 92%
See 2 more Smart Citations
“…Figure summarizes the representative high‐performance polymer acceptors enabling PCEs over 8% in all‐PSCs reported in literature together with their optical bandgap ( E g opt ) and absorption coefficient (ε) . Recently, with the extensive efforts dedicated to polymer design and device optimization, Huang and co‐workers and Jenekhe and co‐workers have achieved all‐PSC performance with PCE greater than 10% using poly(naphthelene diimide‐ alt ‐bithiophene) (N2200) and BSS10 as the acceptor, respectively (Figure a). However, most of the NDI‐ and PDI‐based polymer acceptors exhibit ε values about 3.0–4.8 × 10 4 cm −1 , which are greatly lower than those (1.0–1.3 × 10 5 cm −1 ) of typical nonfullerene small molecules .…”
Section: Figurementioning
confidence: 92%
“…Organic solar cells (OSCs) have achieved long‐term and consistent advance with remarkable power conversion efficiencies (PCEs) of greater than 16% obtained in nonfullerene solar cells, recently . Among various types of OSCs, all‐polymer solar cells (all‐PSCs) consisting of polymers as both donor and acceptor semiconductors show pronounced advantages over other types of OSCs in terms of mechanical flexibility and remarkable device stability . However, the PCEs of all‐PSCs still lag behind those of OSCs based on fullerenes and nonfullerene small molecule acceptors, which is mainly due to the lack of high‐performance n‐type polymer semiconductors.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Several other NDI‐based polymer acceptors were also used for additive‐free all‐PSCs with their device performance parameters summarized in Table . Recently, random copolymerization has been developed as a simple and effective approach to balance various properties of the NDI‐based polymer acceptors from absorption to energy levels and to blend film morphology, exemplified by polymer BSS10 ( 6.3 ), in which two donor units selenophene and biselenophene with a ratio of 1 : 9 were polymerized with NDI to afford the random copolymer . It demonstrated that with a small ratio of selenophene, the polymer chains showed a face‐on predominant orientation, which can promote more efficient charge transport in solar cell devices.…”
Section: Polymer Acceptors For Additive‐free Oscsmentioning
confidence: 99%
“…Thus, all-polymer solar cells (all-PSCs) consisting of a polymeric donor and acceptor have attracted more and more attention and are promising for use in realizing highly efficient and stable solar cells (Kim et al, 2015;Kang et al, 2016;Liu et al, 2016Liu et al, , 2018bLong et al, 2016;Wang et al, 2017;Zhang et al, 2017). Encouragingly, all-PSCs have recently achieved over 10% PCEs (Fan et al, 2017a(Fan et al, ,b, 2018(Fan et al, , 2019bLi et al, 2017a;Zhang et al, 2017;Chen et al, 2018;Kolhe et al, 2019;Li Z. et al, 2019;Meng et al, 2019;Yao et al, 2019;Zhu et al, 2019;Zhao et al, 2020). To date, highly efficient all-PSCs are mostly based on naphthalene diimide (NDI) polymer acceptors, because of their high electron mobility, suitable energy levels, and tunable BHJ morphology Li et al, 2016;Fan et al, 2017a,b;Liu et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%